The Job Satisfaction on Employees at Dinas Perpustakaan dan Kearsipan in Sinjai Regency - Amal, A. Israq Irgyanto; M. Tahir; Seny Luhriyani (International Journal of Business English and Communication, 2024)
This research aims to explore and analyze the level of employee job satisfaction at Dinas Perpustakaan dan Kearsipan in Sinjai Regency. The research subjects consisted of the head of the agency and two employees, with a focus on job satisfaction based on aspects of the job itself, salary, promotions, supervision, and co-workers. The research objectives include an in-depth understanding of current job satisfaction and the ways to increase the job satisfaction of employees. The research method used is qualitative with an interview approach and direct observation. Data is collected through direct interaction with participants and then analyzed to identify emerging patterns and findings. The results of the research show that employees' job satisfaction at Dinas Perpustaakan dan kearsiapan in Sinjai Regency is generally good. Factors such as the work itself, salary, and co-workers have a positive contribution to job satisfaction, while promotions and supervision have a more limited impact. In the ways to increase job satisfaction, this agency has implemented various strategies, including employee training and development, creating a relaxed and pleasant work atmosphere (cool and fun), as well as implementing an organizational culture that encourages values such as teamwork, full innovation, and carrying out the best processes. for best results, showing visitor satisfaction, honesty, trust, enjoyment, and loyalty. The conclusions of this study highlight the importance of paying attention to factors that significantly influence employee job satisfaction. The implications of these findings can be a basis for developing more effective management policies and practices in Dinas Perpustakaan dan Kearsipan in Sinjai Regency.